2017
DOI: 10.1186/s13229-017-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

A few of my favorite things: circumscribed interests in autism are not accompanied by increased attentional salience on a personalized selective attention task

Abstract: BackgroundAutistic individuals commonly show circumscribed or “special” interests: areas of obsessive interest in a specific category. The present study investigated what impact these interests have on attention, an aspect of autistic cognition often reported as altered. In neurotypical individuals, interest and expertise have been shown to result in an automatic attentional priority for related items. Here, we examine whether this change in salience is also seen in autism.MethodsAdolescents and young adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…Neither children nor adults with ASD demonstrated evidence of visual expertise for their interests relative to age-matched NT controls, even though adults with ASD reported spending more time on their interests than NT adults. The findings are similar to prior work demonstrating no differences in attention (Parsons et al, 2017) or learning (Schuetze et al, 2019) for personalized interests in ASD as compared to NT controls, as well as no differences in visual acuity (Tavassoli et al, 2011). Together the findings suggest that while these search tasks captured low-level visual perceptual differences across key variables (i.e., improved performance with age, increasing RT with array size, predominantly parallel processing for category search), differences in low-level visual perception between ASD and NT participants are relatively minor.…”
Section: Discussionsupporting
confidence: 90%
“…Neither children nor adults with ASD demonstrated evidence of visual expertise for their interests relative to age-matched NT controls, even though adults with ASD reported spending more time on their interests than NT adults. The findings are similar to prior work demonstrating no differences in attention (Parsons et al, 2017) or learning (Schuetze et al, 2019) for personalized interests in ASD as compared to NT controls, as well as no differences in visual acuity (Tavassoli et al, 2011). Together the findings suggest that while these search tasks captured low-level visual perceptual differences across key variables (i.e., improved performance with age, increasing RT with array size, predominantly parallel processing for category search), differences in low-level visual perception between ASD and NT participants are relatively minor.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the prevalence and pervasiveness of CIs in ASD, studies investigating this symptom are limited [ 12 ], particularly in adolescence. Behavioural and neuroimaging studies that have investigated CIs often record responses during viewing of images or videos [ 11 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have focused on young children and adults [ 9 11 ] relatively little is known about the expression of CIs in adolescents with ASD and how they compare to the interests of typically developing (TD) adolescents in content and intensity [ 12 ]. CIs are suggested to interact with the development of social behaviour and peer relationships [ 7 , 9 ], and are present in most adolescents with ASD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in older children and adolescents found that autistics visually explored fewer objects with longer fixations, but increased object exploration was correlated with increased RRBs [31]. In adolescents and adults performing a selective attention task, there is also preliminary evidence that in some circumstances autistics may experience less distraction or interference from their intense interests than do typical individuals [32]. This result was contrary to predictions and suggests the importance of improved and more direct tests of when or whether RRBs, which encompass atypical autistic interests, limit or interfere with exploration and attendant learning opportunities in autism.…”
Section: Introductionmentioning
confidence: 99%